Ghost Wars : The Secret History of the CIA, Afghanistan, and Bin Laden, from the Soviet Invasion to September 10, 2001 - Coll, Steve (GHQ, Rawalpindi Army Publishing House, 2010)
An account of the CIA's involvement in the covert wars in Afghanistan that fueled Islamic militancy and gave rise to bin Laden's al Qaeda. For nearly the past quarter century, while most Americans were unaware, Afghanistan has been the playing field for intense covert operations by U.S. and foreign intelligence agencies-invisible wars which sowed the seeds of the September 11 attacks and which provide its context. From the Soviet invasion in 1979 through the summer of 2001, the CIA, KGB, Pakistan's ISI, and Saudi Arabia's General Intelligence Department all operated directly and secretly in Afghanistan. They primed Afghan factions with cash and weapons, secretly trained guerrilla forces, funded propaganda, and manipulated politics. In the midst of these struggles bin Laden conceived and then built his global organization. The author tells the secret history of the CIA's role in Afghanistan, from its covert program against Soviet troops from 1979 to 1989, to the rise of the Taliban and the emergence of bin Laden, to the secret efforts by CIA officers and their agents to capture or kill bin Laden in Afghanistan after 1998. Based on extensive firsthand accounts, this story goes well beyond anything previously published on U.S. involvement in Afghanistan. It chronicles the roles of midlevel CIA officers, their Afghan allies, and top spy masters such as Bill Casey, Saudi Arabia's Prince Turki al Faisal, and George Tenet.
Include Map, Notes, Bibliography and Index
Keywords: Bin Laden, Osama, 1957-2011 -- Afghanistan -- Soviet Occupation of Afghanistan (1979-1989) -- United States. Central Intelligence Agency